Effects of Ginkgo biloba Extract and Bilobalide, a Main Constituent, on the Ionic Currents in Guinea Pig Ventricular Cardiomyocytes - Satoh, Hiroyasu (Arzneimittelforschung, 2003)
Effects of Ginkgo biloba extract (GBE, 0.01 to 1 mg/ml) and a main constituent, bilobalide (0.1 to 1 µmol/l), on the action potentials and the underlying ionic currents in guinea pig ventricular cardiomyocytes were investigated using a patch-clamp technique. Both GBE and bilobalide at high concentrations caused depressant actions on the action potential configuration. GBE (0.3 mg/ml) decreased the Vmax by 17.1 ± 2.1 % (n = 6, p < 0.05), and bilobalide (1 µmol/l) by 14.7 ± 2.2 % (n = 8, p < 0.05). GBE prolonged the action potential duration at 90 % repolarization (APD90), by 70.6± 2.8 % (n = 6, p < 0.001) at 1 mg/ml; in contrast, bilobalide shortened APD, by 11.1 ± 2.0 % (n = 8, p < 0.05) at 3 µmol/l. In voltage-clamp experiments, GBE (1 mg/ml) markedly inhibited the Ca2+ current (ICa) at 10 mV by 90.1 ± 3.0 % (n = 6, p < 0.001), the delayed rectifier K+ current (IK) at 60 mV by 63.7 ± 3.0 % (n = 6, p < 0.01), and the inwardly rectifying K+ current (IK1) at −120 mV by 47.8 ± 2.6 % (n = 6, p < 0.01). On the other hand, bilobalide at 1 µmol/l enhanced the ICa by 40.0 ± 2.3 % (n = 6, p < 0.05), and the IK by 14.0 ± 2.3 % (n = 6,p < 0.05), concentration-dependently. The IK1 was unaffected. These responses were reversible (to approximately 50−80 %) after 10- to 2-min washout. These results indicate that even after acute administrations, GBE and bilobalide produced active actions on the APD and the ionic currents in cardiomyocytes. Although each chemical exhibited the responses in opposite directions, GBE acts totally as a mixture.
Keywords: Bilobalide, effects on action potential and ionic currents, guinea pig ventricular cells; Gingko biloba extract, effects on action potential and ionic currents, guinea pig; ventricular cells; Ginkgolon-24®